A look of otherness in Bakhtin: The study of the utterance as a form of dialogue - Mussio, Simone [UNESP] (Univ Estado Rio Janeiro, 2015)
Being the founding principle of the dialogic theory of discourse the philosophy of dialogue, which sees the man not as an individual but as one that is constituted through the dialogic relationship between an I and a you, every enunciation, according to this theoretical concept, becomes dialogic in nature. As the dialogism is considered the order of the enunciation, this does not close itself off, but is made through the endless dialogue between other enunciations that precede or succeed it in the discursive chain. Thus, based upon this otherness present in the discursive constitution, this paper aims, from a literary exhibition about the subject, discuss and reflect the bakhtinian precepts, taking in the concept of enunciation, anchored in speech genres, the genesis of an enunciation theory that, based on the enunciation of conditions and on the interlocutors involved, ensures the enunciation a historic univocally determined by the specific verbal interaction contexts. Therefore, Bakhtin's criticisms regarding the two central guidelines of philosophical-linguistic thinking, idealistic subjectivism and abstract objectivism are portrayed, as well as the differentiation between the concepts of word and clause to finally conduct a dialogue on the boundaries of the concrete utterance, which is seen as a key element of verbal communication.
Keywords: Enunciation; Dialogic theory of discourse; Bakhtin; Dialogism